Cross platform Social Media Management: A Case Study on Cyber Public Relations Implementation of Indonesia’s Private TV Station in Building External Stakeholders Engagement - Susilo, Anindita; Fauzy, Ahmad (Technium Social Sciences Journal, 2021)
As a media company, Metro TV implemented Cyber Public Relations activities in order to build engagement with the public. The engagement value between Metro TV and its followers on the three social media accounts are able to reach high number. This study aims to see the implementation of cyber public relations by Metro TV as a media company in building public engagement on social media. This study uses the concept of Public Relations management initiated by Cutlip which is then linked to the concept of Cyber PR and engagement. The research method used is case study with a qualitative approach. Data were collected through in-depth interviews with Metro TV’s Head of Public Relations as key informants, Metro TV social media specialists and Metro TV social media followers as supporting informants. The data and information obtained from the interviews will be analyzed using the stages of data reduction, data presentation, and conclusion drawing. The results of this study indicated that the implementation of Metro TV cyber public relations focuses on 4 main activities, there are: forming engagement and interaction spaces, creating digital campaigns and education, publishing internal company activities, and crisis mitigation. In addition, the implementation of cyber public relations of Metro TV in creating public engagement on social media includes engaging key opinion leaders from internal companies, mirroring content on various platforms, monitoring engagement level and insights on social media, as well as producing relevant and the human side contained content. And finally, the management of social media as a form of implementation of Metro TV cyber public relations is carried out in 3 stages, including: pre-production, production and post-production.